2012
DOI: 10.1097/mat.0b013e31826a87bc
|View full text |Cite
|
Sign up to set email alerts
|

Can Learning to Interpret Pump Messages Help Lead to an Early Diagnosis of HeartWare Ventricular Assist Device Thrombosis?

Abstract: Left ventricular assist device thrombosis is a detrimental complication that, if not properly diagnosed and treated, can lead to low output syndrome and death. When ongoing thrombus formation is caused by inappropriate anticoagulation, timely identification is possible, and could perhaps be the key to successful treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 4 publications
1
13
0
Order By: Relevance
“…The growth rate of the power is a previously unused method of gauging the thrombus severity. In this study, medical therapy was most often successful when both the power and growth rate measurements were low ( Figure 3, Table 1) which concurs with the qualitative experiences of single centers (14).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The growth rate of the power is a previously unused method of gauging the thrombus severity. In this study, medical therapy was most often successful when both the power and growth rate measurements were low ( Figure 3, Table 1) which concurs with the qualitative experiences of single centers (14).…”
Section: Resultssupporting
confidence: 88%
“…For patients with the HVAD system, the consistent power increase during a build-up thrombus could be used for early identification (13,14,21). The growth rate of the power is a previously unused method of gauging the thrombus severity.…”
Section: Resultsmentioning
confidence: 99%
“…There were 20 reported deaths in this group of patients. 4,15,2023,26,27,4262 Thrombolytics were used as a triple or a quadruple drug therapy (i.e. in combination with IV UFH and either GPIIb/IIIa inhibitor and/or direct thrombin inhibitor) in 18 patients resulting in a complete resolution in 56% (10/18) of patients.…”
Section: Resultsmentioning
confidence: 99%
“…The clinical presentation of HVAD thrombosis is based on relatively limited evidence and depends on the origin of the thrombus. Abnormally increased power consumption and increased estimated pump flow were associated with thrombosis in most cases with HVAD support [45][46][47]; however, both a progressive increase in flow with stable power resulting in reduction of the head pressure [48] and reduction in pump flow with gradual increase in power [49] have been shown in individual reports. Clinical symptoms are unspecific and can include dyspnea, fatigue, peripheral edema, ascites and worsening renal function.…”
Section: Device Thrombosismentioning
confidence: 96%
“…In the authors' institution, with an audible rumbling sound from the HVAD was reported in several patients with device thrombosis, which may also be helpful in diagnosis. Echocardiography, the most common imaging technique for thrombosis diagnostics, is not always sufficient for adequate visualization of the inflow cannula and thrombus formation itself [50], but may provide information on consequences of pump obstruction, such as decompensation of left heart and frequent aortic valve opening and interventricular septal shift to the right due to insufficient unloading of the LV [45][46][47][48][49]. Further echocardiographic criteria of potentially dysfunctional devices, as could be seen from the example of HeartMate II LVAD, might be decreased basic diastolic CF velocity in inflow and outflow cannulas (up to 15-20 mm/s, whereas the normal range varies between 100 and 200 cm/s) with a pulsatile increase in flow velocity during ventricular contraction, increased left-ventricular end-diastolic and end-systolic dimension, increased left-ventricular ejection time and aortic valve amplitude and higher grade of mitral regurgitation [51].…”
Section: Device Thrombosismentioning
confidence: 99%